Cellular Technologies in Traumatology: from Cells to Tissue Engineering - N. N. Dremina; I. S. Trukhan; I. A. Shurygina (Acta Biomedica Scientifica)
Severe injuries of the musculoskeletal system with damage of bone and cartilaginous tissue are associated with the necessity to find ways for replacement of defects. Current methods of treatment including the usage of autografts and modern synthetic materials are often not effective enough. The article deals with the prospects for developing the new areas in the traumatological pathology treatment based on the cell technologies application. Both medical and ethical aspects of the cell technology usage and the utilizing various sources of cell material for transplantation are discussed in detail. Special attention is devoted to application of the mesenchymal stem cells as  the most suitable material for bone and cartilage repair. These cells possess the properties of multipotent stem cells that can adhere to plastic surfaces, differentiate into various cells, including chondroblasts, osteoblasts, and migrate to the damaged area. It is shown that the number and biological characteristics of the isolated cells depend on the tissue, the cell isolation method, and the culture medium. During the cultivation of mesenchymal  stem cells, the true marker of which is Stro-1, it is necessary to monitor the duration and number of passages, because these values are inversely correlated with the differentiating potential of cells, and spontaneous transformation according to oncogenic pathway may occur. Thus, mesenchymal stem cells represent a current material for the reconstruction of hard tissues. Despite ethical and technological problems, cell technologies are a promising approach in regenerative medicine.